Application of the MELTS algorithm to Martian compositions and implications for magma crystallization. Issue 12 (23rd December 2013) - Balta, J. Brian; McSween, Harry Y.
Abstract [1] The MELTS algorithm, the most commonly used tool for calculating crystallization of basaltic magmas, uses thermodynamic parameters calibrated by experiments on select compositions, and thus, its use on newly discovered extraterrestrial compositions requires extrapolation across ranges where its applicability has not been evaluated in detail. To apply MELTS to Martian compositions, we undertook a systematic examination of the original MELTS calibration and the pMELTS revision as applied to Martian magmas. We find that the algorithm is effective in predicting the crystallization paths and conditions of Martian magmas, with some issues. The algorithm consistently overestimates the stability of spinel and underestimates pressures of multiple saturation compared to experiments. The pMELTS calibration comes close to fitting multiple‐saturation pressures but cannot be used at low pressures. Both calibrations model crystallization temperatures with similar variances to those observed for terrestrial compositions. Both calibrations reproduce important compositional details of crystallizing magmas and coexisting minerals with errors similar to those observed on terrestrial compositions. We calculate several crystallization paths which predict high‐FeO, high‐density magma compositions that could be a mechanism for cumulate formation. Low‐FeO compositions in recent Mars volcanism may be an expression of this density barrier. However, the composition of a high‐FeO rock called "Et‐Then" discovered by the rover Curiosity is strikingly similar to compositions calculated by the MELTS algorithm and could represent one of these high‐FeO volcanic rocks.